2018
DOI: 10.1080/20008198.2018.1425574
|View full text |Cite
|
Sign up to set email alerts
|

Intensive prolonged exposure therapy for chronic PTSD patients following multiple trauma and multiple treatment attempts

Abstract: Background: Suboptimal response and high dropout rates leave room for improvement of trauma-focused treatment (TFT) effectiveness in ameliorating posttraumatic stress disorder (PTSD) symptoms. Objective: To explore the effectiveness and safety of intensive prolonged exposure (iPE) targeting chronic PTSD patients with a likely diagnosis of ICD-11 Complex PTSD following multiple interpersonal trauma and a history of multiple treatment attempts. Method: Participants (N = 73) received iPE in 12 × 90-minute session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 72 publications
(97 reference statements)
12
65
1
Order By: Relevance
“…These findings are in accordance with a wide array of previous studies on massed treatment showing the feasibility, safety, and effectiveness of such an approach (e.g. Ehlers et al, 2014; Hendriks et al, 2018, 2016; Zepeda Méndez et al, 2018; Zoellner et al, 2017). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in accordance with a wide array of previous studies on massed treatment showing the feasibility, safety, and effectiveness of such an approach (e.g. Ehlers et al, 2014; Hendriks et al, 2018, 2016; Zepeda Méndez et al, 2018; Zoellner et al, 2017). …”
Section: Discussionsupporting
confidence: 92%
“…Indeed, several studies investigating the feasibility of intensive CBT in these populations have shown positive results regarding the treatment of PTSD (e.g. Hendriks, De Kleine, Broekman, Hendriks, & Van Minnen, 2018; Zoellner et al, 2017; for a review see Hendriks, De Kleine, Hendriks, & Van Minnen, 2016). In a meta-analysis, EMDR was found to be effective for complex trauma (Chen et al, 2018) but little is known about the effects of intensive EMDR therapy.…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing both analyses, this exploratory study examined both overall outcomes and addressed an important question of how overall results are modulated by trauma exposure severity. Existing literature indicates that trauma exposure severity and chronicity may be important considerations in the maintenance and treatment of PTSD symptoms in various populations (Bedard-Gilligan et al, 2015;Hendriks, De Kleine, Broekman, Hendriks, & Van Minnen, 2018;Jakob, Lamp, Rauch, Smith, & Buchholz, 2017). The current findings, although preliminary and exploratory, add to the developing literature by showing that oxytocin dampens amygdala reactivity to fear cues among more severely childhood-trauma exposed individuals with PTSD, thus providing modest support for the premise that oxytocin may target neural mechanisms of resilience and recovery in this particularly highrisk population.…”
Section: Discussionsupporting
confidence: 44%
“…None of the patients dropped out during the intensive phase, and 5% of the patients dropped out during the booster phase. The specific details on the population and treatment effects are reported elsewhere (Hendriks, Kleine, Broekman, Hendriks, & Minnen, 2018). …”
Section: Examplementioning
confidence: 99%